SATIRICAL ELEMENTS IN THE ALBUM ”TO PIMP A BUTTERFLY” BY KENDRICK LAMAR - Anugrah, Muh. Andre; Nur, Riola Haya (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Contemporary hip-hop has established itself as one of the most powerful forms of social commentary in popular music, yet limited scholarly attention has been paid to how satirical techniques specifically function within contemporary albums as both artistic devices and tools for social critique. This study examines the satirical elements in Kendrick Lamar's 2015 album